CMC with Pregnancy - A case report - Rahman, MM; Jalaluddin, SM; Hossian, L; Amran, A; Kalam, A; Ahsan, S; Islam, S; Begum, S (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v1i1.13306 KYAMC Journal Vol.1(1) July 2010, 34-35